Análise de indícios de alfabetização científica no desenvolvimento de projeto STEAM: olhando para as meninas na ciência - Inácio, Érica Fátima (2024)
The increase in the number of women in the labor market has been a prevailing trend in Brazil in recent years. Nonetheless, the literature underscores the invisibility of women in science and their integration into the workforce. The ascent of women in this domain remains symbolic vis-à-vis the extensive spectrum of opportunities available. One plausible explanation for the gender disparity may be attributed to societal stereotypes suggesting divergent aptitudes for specific career paths between genders. These stereotypes have adversely affected the motivation and interest of female students in scientific disciplines during their educational trajectory. Against this backdrop, the research aims to probe the following inquiry: What manifestations of Scientific Literacy can be discerned in the execution of a project from the STEAM perspective by female students in Middle School II? The scrutinized project, titled "Readings: a platform aiding in alleviating reading challenges for children with ADHD and dyslexia," was conceived and implemented by three female students in the 9th grade of Middle School II. This endeavor addressed tangible issues, offering contextualized and interdisciplinary content, endeavoring to proffer feasible solutions or prototypes. The research data were amassed during Integrated Axis sessions at a SESI school situated in the hinterlands of São Paulo state. Data gathering transpired through a journal maintained by participating students and supplemented by an interview conducted by the instructor-researcher. Data analysis was underpinned by the categories of Scientific Literacy (SL) entwined with the aims and objectives of science education, encompassing practical, civic, and cultural dimensions. Besides these, additional dimensions pertinent to the acquisition of scientific knowledge were assimilated, such as functional, conceptual, procedural, and the overarching multidimensional dimension. Across the project's duration, signs of Scientific Literacy permeated all categories. The students evinced progressive development in scientific knowledge and prowess, alongside embracing a more discerning stance consonant with the tenets of Scientific Literacy. These findings underscore the imperative of fostering and bolstering female participation in STEAM initiatives, with the aim of catalyzing heightened interest and motivation in scientific disciplines and advancing gender parity in the realms of science and technology. Furthermore, they underscore the significance of Scientific Literacy as an instrument for empowering youth to comprehend and actively engage in the scientific and technological milieu, thereby contributing to the cultivation of a more critically engaged society. Keywords: Scientific Literacy; Science; Elementary Education; Girls; STEAM.